IMPLEMENTATION OF COMMUNICATIVE IMPACT IN THE ENGLISH-LANGUAGE POPULAR SCIENCE IT-DISCOURSE - Marina L. Avakova; Nadezhda B. Ayvazyan (Sovremennye Issledovaniâ Socialʹnyh Problem)
Background. The article is devoted to the study of the implementation of communicative impact in the English-language popular science IT-discourse. The study is relevant due to the development of new possibilities of communicative interaction, the increasing social role of information in the global digital environment. Professional communication concentrated on various features of modern information technologies plays an important role in the dissemination of scientific knowledge to the public.